Investigation of Anticancer Activity of Ochratoxin Against Prostate Cancer Cell Line - Türkmen, Neşe Başak; Küçük, İrem Sena; Taskın, Irmak Icen; Yaşar, Şeyma; Özek, Dilan Aşkın; Yüce, Hande (İnönü Üniversitesi, 2025)
Prostate cancer is one of the most prevalent malignancies among men and remains a significant public health concern due to its high mortality rate, despite the availability of current treatment strategies. Ochratoxin, a naturally occurring mycotoxin, has attracted considerable attention for its diverse biological activities. This study explores the anticancer potential of ochratoxin in prostate cancer cell lines. Cell viability was evaluated following treatment with defined concentrations of ochratoxin, and apoptotic mechanisms, along with gene expression profiles, were analyzed. The results demonstrate that ochratoxin suppresses cell proliferation and induces apoptosis in a dose-dependent manner. These findings suggest that ochratoxin may represent a promising candidate for prostate cancer therapy. However, further in vivo studies are necessary to confirm its clinical relevance and therapeutic applicability.
Keywords: Toxicology; Toksikoloji